European Football Player Transfer Scheme according to IFRS and IAS: Case Study on Juventus Football Club S.p.A - Limba, Franco Benony; Sapulette, Shella Gilby (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Recognition of soccer players as intangible assets in financial statements is still happening today, this case will affect the accounting treatment that will be received by player transfer activities from the old club to the new club. The purpose of this study is to analyze the transfer scheme of football players in Europe from the perspective of IFRS and IAS accounting regulations. This study uses secondary data in the form of player transfer data for the Italian football club Juventus Football Club S.p.A in the 2018/2019 to 2020/2021 season which is included in the club's annual financial statements. In addition, it also uses IFRS and IAS as a study in providing solutions to transfer activities experienced by European clubs. The results of this study indicate that European football players can be categorized as intangible assets and receive proper treatment as intangible assets. Although football activities are different from the industry in general, the transfer scheme carried out by the club can be explained as recognized under IFRS and IAS regulations and used by the club in its financial statements legally.